KECERDASAN FINANSIAL CALON INVESTOR LQ-45 - Ratnawati, Tri; Aprilianto, Deni; Luqyana, Ikbar (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2020)
Financial intelligence is the ability to manage funds that benefit in achieving prosperity. The purpose of this study was to determine the intelligence of prospective LQ 45 investors in investment decision making using Saussure langue and parole structuralism theory. This research method uses a qualitative narrative method. Data collection using interview techniques. Research findings correspondent have different financial intelligence. Based on educational background the correspondents represented different understanding. Consideration of investment decisions is not just stock information (langue) which is the basis of decision (parole). News and information from experts are also a consideration. Not only can everyone be influenced by langue, financial intelligence also influences parole. This finding supports with the same information but produces different decisions. Keywords: Financial Intelligence, Langue, Parole, Investment Decision, and LQ 45